Time series analysis of economic traits in Sahiwal cattle - GANDHI, R S; SINGH, SURENDRA; SACHDEVA, G K (The Indian Journal of Animal Sciences, 2011)
The data on 2144 lactation records of 681 Sahiwal cows spread over 42 years (1965–2005) were analyzed for evolving correction factors to adjust the data for non-genetic factors by time series analysis. The traits considered were age at fist calving (AFC), lactation total milk yield (LTMY), lactation 305–day or less yield (L305DMY), lactation length (LL), calving interval (Cl) and service period (SP). The overall least squares population means for these traits were 1155.07±20.51 days, 2162.68±25.39 kg, 2030.19±19.96 kg, 295.71±2.61 days, 410.63±3.57 days and 119.57±3.31 days, respectively. The seasonal and cyclical components of these traits were isolated. A periodicity of 7, 5, 6, 7, 7 and 5 years was observed in the above traits. The periodic function was fitted and it explained maximum variation in the above traits ranging from 27.89% (LL) to 83.77% (AFC) revealing the periodicity of data over the years for majority of traits. Hence, animal breeding data has to be adjusted for cyclicity over the years. Further, the monthly/seasonal indices estimated by ratio to trend method accounted for more environmental fluctuations and were more appropriate for decomposing the time series data than link relative metho